2006
DOI: 10.1007/s11249-006-9101-0
|View full text |Cite
|
Sign up to set email alerts
|

EHL simulation using the free-volume viscosity model

Abstract: The free-volume viscosity model can accurately predict the temperature-pressure-viscosity relationship of lubricants. However, it is seldom used in elastohydrodynamic lubrication (EHL) simulation. This paper presents the application of the free-volume viscosity model in a Newtonian EHL simulation of a squalane-lubricated circular contact. Good agreement is observed between available experimental data and simulation results. The pressure-viscosity coefficients fit from viscometer data are also discussed. A rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…[43][44][45][46][47][48][49][50][51][52] In cases where an existing experimental data set was repeated (or it appeared that the same point was not re-measured) in subsequent articles, only the original data set was included in the regression data set: 64 , where there was a very limited data set available for the development of a reference model, the abundance of experimental data for squalane made it unnecessary to include molecular simulations in this work. 37,[65][66][67][68][69][70][71][72][73] Two points from Whitmore et al (1966) 8 were not included due to the inability of converting kinematic viscosities of sub-cooled squalane (219 and 233) K.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50][51][52] In cases where an existing experimental data set was repeated (or it appeared that the same point was not re-measured) in subsequent articles, only the original data set was included in the regression data set: 64 , where there was a very limited data set available for the development of a reference model, the abundance of experimental data for squalane made it unnecessary to include molecular simulations in this work. 37,[65][66][67][68][69][70][71][72][73] Two points from Whitmore et al (1966) 8 were not included due to the inability of converting kinematic viscosities of sub-cooled squalane (219 and 233) K.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently [11], the film thickness in point contact for squalane was accurately calculated from the coupled Reynolds and elasticity equations. Squalane is a monodisperse, low-molecular-weight liquid, known to possess a sufficiently large Newtonian limit, G& 6 MPa [12], that the behavior within the inlet zone, which determines film thickness, may be assumed to be Newtonian.…”
Section: Introductionmentioning
confidence: 99%
“…Several definitions of the pressure-viscosity coefficients 66 were used for this aim: the local pressure-viscosity coefficient at different pressure conditions (0.1 MPa or another pressure) or the piezoviscous coefficient highest, among others. Bair et al 66 and Liu et al 68 showed that the definition of film given by equation (16) In order to analyze the effect of the lubricant in the central thickness (hc), we have used the following equation 64 proposed by the American Gear Manufactures Association (AGMA) for calculation of hc:…”
Section: Resultsmentioning
confidence: 99%